INTEGRASI MATA PELAJARAN CODING DAN KECERDASAN BUATAN (AI) DALAM KURIKULUM SEKOLAH DASAR SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN ABAD KE-21 - Wilda Rizkiyahnur Nasution; Aslan Aslan (Adiba Aisha Amira, 2025)
The development of digital technology demands a paradigm shift in education, particularly in preparing young people to master 21st-century skills such as critical thinking, creativity, collaboration, and digital literacy. This study aims to analyse the implementation of coding and artificial intelligence (AI) integration in primary school curricula as a strategy to improve these skills. The research method used is a literature review. The results indicate that the integration of coding and AI can strengthen both technical and soft skills among students, despite challenges such as infrastructure limitations and teacher readiness. This study recommends the development of age-appropriate learning materials, intensive teacher training, and equitable access to technology to ensure effective and sustainable integration. Thus, the integration of coding and AI in primary schools is a crucial investment in cultivating adaptive and competent generations in the digital age.